Thiadiazoline- and Pyrazoline-Based Carboxamides and Carbothioamides: Synthesis and Inhibition against Nitric Oxide Synthase - Fabio Arias; M. Encarnación Camacho; M. Dora Carrión; Meriem Chayah; Miguel Romero; Juan Duarte; Miguel A. Gallo (Journal of Chemistry)
Two new families of pyrazoline and thiadiazoline heterocycles have been developed. Their inhibitory activities against two different isoforms of nitric oxide synthase (inducible and neuronal NOS) are reported. The novel derivatives were synthesized combining the arylthiadiazoline or arylpyrazoline skeleton and a carboxamide or carbothioamide moiety, used as starting material ethyl 2-nitrobenzoates or substituted nitrobenzaldehydes, respectively. The structure-activity relationships of final molecules are discussed in terms of the R1 radical effects in the aromatic ring, the Y atom in the heterocyclic system, the X heteroatom in the main chain, and the R2 substituent in the carboxamide or carbothioamide rest. In general, thiadiazolines (5a–e) inhibit preferentially the neuronal isoform; among them, 5a is the best nNOS inhibitor (74.11% at 1 mM, IC50 = 420 μM). In contrast, pyrazolines (6a–r) behave better as iNOS than nNOS inhibitors, 6m being the best molecule of this series (76.86% at 1 mM of iNOS inhibition, IC50 = 130 μM) and the most potent of all tested compounds.